Dispersion of modified fumed silica in elastomeric nanocomposites. (3rd January 2023) - Okoli, Ugochukwu; Rishi, Kabir; Beaucage, Gregory; Kammler, Hendrik K.; McGlasson, Alex; Chauby, Michael; Narayanan, Vishak; Grammens, James; Kuppa, Vikram K.
Abstract: In polymer nanocomposites, surface modification of silica aggregates can shield Coulombic interactions that inhibit agglomeration and formation of a network of agglomerates. Surface modification is usually achieved with silane coupling agents although carbon-coating during pyrolytic silica production is also possible. Pyrogenic silica with varying surface carbon contents were dispersed in styrene-butadiene (SBR) rubber to explore the impact on hierarchical dispersion, the emergence of meso-scale structures, and the rheological response. Pristine pyrogenic silica aggregates at concentrations above a critical value (related to the Debye screening length) display correlated meso-scale structures and poor filler network formation in rubber nanocomposites due to the presence of silanol groups on the surface. In the present study, flame synthesized silica with sufficient surface carbon monolayers can mitigate the charge repulsion thereby impacting network structural emergence. The impact of the surface carbon on the van der Waals enthalpic attraction, a ∗, is determined. The van der Waals model for polymer nanocomposites is drawn through an analogy between thermal energy, kB T, and the accumulated strain, γ . The rheological response of the emergent meso-scale structures depends on the surface density of both carbon and silanol groups. Graphical abstract: Image 1 Highlights: Silica with low or no carbon coverage display correlation in elastomer nanocomposites. With 2–3 monolayers of carbon charge repulsion is shielded for a random distribution. Emergent filler network structure can be tuned by surface carbon coverage. van der Waals approach quantifies interactions as a function of surface chemistry. Rolling resistance and wet grip show similar dependence on surface chemistry.